Lived experience of pedagogical boomerang in mathematics teaching-learning - Sher Singh Rawat; Bal Chandra Luitel; Shashidhar Belbase (Journal of Education and Learning (EduLearn), 2021)
The purpose of this study was to explore the critical life-events of the first author's journey of learning and teaching mathematics that prompted critical thinking about his past experiences as a student and teacher. It portrays a paradigmatic shift from a traditionalist thinker to a constructivist actor in the classroom from the critical life-events within and out of classroom experiences by using autoethnography as the writing and research genre by connecting his personal experiences in the social, cultural, and teaching/learning contexts of Nepal. The major themes emerged from the autoethnography were-- Thinking Narratively: Joining a School and Dropping Out; Thinking Narratively: Back to School and Dropping In; Thinking Interpretively: Dropping out of School; Thinking Poetically: Dropping in School; and Nightmare of the First Teaching: A Pedagogical Boomerang. These themes portrayed a pedagogical boomerang in learning and teaching mathematics from a remote village in Western Nepal to the neighborhood of the capital city Kathmandu.